STRATEGY FOR IMPROVING THE QUALITY OF GRADUATES - Afif Alfiyanto; Selvia Assoburu; Maryance; Samuel Urath; Muhammad Ghazali (Jurnal Konseling Pendidikan Islam, 2022)
The purpose of this study is to identify strategic planning's role in raising graduation quality as well as supportive and impeding elements. The principal of the school serves as the major informant source for this qualitative study, with the perspectives of students and instructors serving as supporting informants. The data was gathered via observation, interviews, and documentation. Data reduction, data presentation, and conclusion are three of the data analysis approaches employed together. According to the study's findings, SMAN 1 Semende Darat Laut has been doing a good job of strategically preparing to raise the quality of its graduates. This is apparent from the strategic planning completed, including a boost in teacher proficiency, new educational initiatives, enhanced facilities and infrastructure, and extracurricular growth. The desire to encourage ongoing education, excellent leadership between leaders and subordinates, and all instructors having college degrees are supportive elements. The lack of resources, infrastructure, and time for extracurricular activities, in contrast, are the issues that prevent students from graduating.